2004
DOI: 10.1038/nature03027
|View full text |Cite
|
Sign up to set email alerts
|

Random quasi-phase-matching in bulk polycrystalline isotropic nonlinear materials

Abstract: Three-wave mixing in nonlinear materials--the interaction of two light waves to produce a third--is a convenient way of generating new optical frequencies from common laser sources. However, the resulting optical conversion yield is generally poor, because the relative phases of the three interacting waves change continuously as they propagate through the material. This phenomenon, known as phase mismatch, is a consequence of optical dispersion (wave velocity is frequency dependent), and is responsible for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
245
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(270 citation statements)
references
References 20 publications
11
245
1
1
Order By: Relevance
“…Chirped QPM gratings have been utilized to manipulate short pulses both in second harmonic generation (SHG) [9,10,11], difference frequency generation (DFG) [12], and in parametric amplification [10,13]. Recent application showed that by using a disordered material (random QPM), an extreme broad bandwidth was obtained, although at a price of severe reduction of the conversion efficiencies [14]. While in standard frequency conversion processes, the crystal parameters and the pump intensity should be precisely matched in order to reach high conversion efficiency, here, by utilizing adiabatic frequency conversion one can still reach near to 100% conversion efficiency over a broad wavelength and temperature range.…”
mentioning
confidence: 99%
“…Chirped QPM gratings have been utilized to manipulate short pulses both in second harmonic generation (SHG) [9,10,11], difference frequency generation (DFG) [12], and in parametric amplification [10,13]. Recent application showed that by using a disordered material (random QPM), an extreme broad bandwidth was obtained, although at a price of severe reduction of the conversion efficiencies [14]. While in standard frequency conversion processes, the crystal parameters and the pump intensity should be precisely matched in order to reach high conversion efficiency, here, by utilizing adiabatic frequency conversion one can still reach near to 100% conversion efficiency over a broad wavelength and temperature range.…”
mentioning
confidence: 99%
“…However, their simplicity, compared to other nonlinear tunable devices based on more sophisticated superstructures of inverted domains, makes them attractive sources for the development of advanced multi-photon devices. [1][2][3][4][5][6][7] Substantially less explored is the capability of these systems to manipulate and control the polarization state of the generated nonlinear beams in a broad frequency range. The simultaneous presence of two or more different phase matching processes, involving different polarization states, is of interest in many applications.…”
mentioning
confidence: 99%
“…The initial characterization and selection of the best part is much desired so as to derive maximum efficiency in further applications. Apart from the applications, where some special types of aperiodicity are necessary (for example, Fibonacci-or Cantor-type nonlinear gratings [23][24][25], stochastic disordered structures [2,[25][26][27]), a higher regularity is required. Thus, it is appropriate to select the regular parts by analyzing the visible nonlinear signal, and then to recommend this part for applications in other spectral ranges.…”
mentioning
confidence: 99%